PSYCHOMETRIC TESTING APPLICATION USING MACROMEDIA FLASH MX - Watik Watik; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Multimedia is a new concept and technology in the field of information technology where text, images, sound, animation, and video incorporated into the computer to be stored, processed and presented attractively.  Psychometric Test applications can help provide facilities for the general public dalammengenali individual personality characteristics and the extent to which intelligence had been.